Elevated Levels of Oxidative Nucleic Acid Modification Markers in Urine From Gastric Cancer Patients: Quantitative Analysis by Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry - Chen, Qin; Hu, Yiqiu; Fang, Zhihao; Ye, Minfeng; Li, Jingqing; Zhang, Suzhan; Yuan, Ying; Guo, Cheng (Frontiers in Chemistry, 2020)
Oxidative nucleic acid modifications have attracted increasing attention in recent years since they have been found to be related to a number of diseases including cancer. 8-Hydroxy-2’-deoxyguanosine (8-OHdG) and 8-hydroxyguanosine (8-OHG) are the typical markers of oxidative modification of DNA and RNA, respectively, and they are emerging biomarkers for early detection of diseases. Urine is a favored biofluid for biomarker discovery due to its noninvasiveness to patients. Accurate quantification of these oxidative nucleic acid modifications still has challenges because their amounts in urine are very low and the interferences in urine samples are complicated. Herein, we developed and validated an accurate and robust solid-phase extraction (SPE) coupled with ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for simultaneous quantification of these oxidative nucleic acid modifications in human urine. Stable isotope dilution strategy was utilized and the method shows good precision on intra-day and inter-day measurements. Meanwhile, recovery was satisfactory by utilizing Oasis hydrophilic-lipophilic balance (HLB) cartridge for sample pretreatment at three spiked levels. We successfully quantified urinary 8-OHdG and 8-OHG from 60 gastric cancer patients and 70 healthy controls by using this method. The measured contents of 8-OHdG and 8-OHG in urine from gastric cancer patients are both increased, compared with those in urine from healthy controls, indicating these oxidative nucleic acid modifications could act as potential noninvasive markers for early diagnosis of gastric cancer. Moreover, the present study will stimulate investigations of the effects of oxidative stress and nucleic acid modifications on the initiation and progression of gastric cancer.